Preliminary Design of a Climate Controlled Environmental Test and Measurement - Lázár, Bence; Szabolcsi, Róbert; Menyhárt, József (Recent Innovations in Mechatronics, 2023)
Climate chambers play an important role in the design and testing process. Several different chambers have been built over the years, specialising in different areas. It means there is a wide choice on the market and as a consequence, parameters necessary for us limit when choosing the ideal test chamber. Our instruments might be subjected to several environmental effects which require a lot of time and effort to be tested. An example is the Mars rover. NASA’s Perseverance Mars rover was equipped with 2 pieces of Li-ion battery packs and the old solar charging was replaced by RTG (Radioisotope Thermoelectric Generator) thus a generator feeds the electricity consumers of the rover. Temperature on the surface of Mars varies from -150 C° to 20 C°. In addition, there are huge storms at regular interval lasting for month sometimes. These storms cause great difficulties because, on the one hand, the main power source on older types was the solar panels, and storms can cover them with Martian dust, limiting or eliminating their power supply. On the other hand, large sandstorms can completely cover the rover, and once the sandstorm is over, the Mars rover has to free itself from its trap. In addition, there were many other factors that engineers had to consider in the design. It is a well-known fact that we are not able to consider all the possible environmental conditions in design, and it is also known that some measurements may be inaccurate, so the prototypes produced have to be tested on the ground. The ground tests must ensure that the operating conditions on Mars are maintained. Special test chambers have been developed for this purpose. [1] The aim of the authors is to design and build a prototype of a climate chamber of their own design. An important component of the chamber is a measurement data acquisition system, which allows the collection of measured data and their preliminary processing.